Evaluating Teacher Preparation Programs in Scientific Disciplines at the Faculty of Education in Al-Aqsa University in Light of the Requirements of the Labor Market (Journal of the College of Education for Women, 2022)
The current study seeks to evaluate teacher preparation programs in the scientific disciplines at the College of Education in Al-Aqsa University in the light of the requirements of the labor market. It further aims to reveal the significance of the differences in the sample members’ response averages of to the availability of labor market requirements in the program that prepares the teacher of scientific disciplines at the Faculty of Education in Al-Aqsa University taking into account the (gender, program) variables. The study followed the descriptive analytical approach, and so a questionnaire was distributed to a sample of scientific discipline students in the teacher preparation program adopted in Al-Aqsa University, (200) male and female students. The study has reached a number of findings that confirm the availability of labor market requirements, particularly those related to vocational, literacy, and life skills in the program adopted. Their response amounted to (75.7%), which is a large percentage. The most important results showed that there was no difference in the responses of the members of the study sample regarding the availability of labor market requirements in teacher preparation programs taking into account the variables of gender and specialization. The results of the study have also revealed that the programs for preparing the teachers of scientific disciplines are largely compatible with the requirements of the labor market. The total percentage of the dimension of harmonizing the programs of the labor market to the teacher preparation programs of scientific disciplines at the College of Education in Al-Aqsa University in the governorates of Gaza reached (70.7%).